Information Asymmetry, Group Cohesiveness, and Budgetary Slack: A Moderating Effect of Budgetary Participation - Jalaluddin, Jalaluddin; Juanda, Juanda; Utami, Lia (Journal of Accounting Research, Organization and Economics, 2020)
Objective The purpose of this study is to examine whether information asymmetry and group cohesiveness affect budgetary slack with budgetary participation as a moderating variable.Design/methodology This research was conducted in a public hospital in Banda Aceh, Indonesia. This study uses primary data in the form of questionnaire which were filled by 38 respondents who were involved in the hospital budgeting process. The samples are selected through simple random sampling methods. The Moderated Regression Analysis (MRA) was utilized to analyze the data.Results The result of this study shows that partially information asymmetry and group cohesiveness influence budgetary slack at a public hospital in Banda Aceh, Indonesia. By using moderated regression analysis with interaction test, the budgetary participation is able to moderate information asymmetry and group cohesiveness towards budgetary slack at a public hospital in Banda Aceh.